Structural feasibility of Expanded Polystyrene (EPS) based lightweight concrete sandwich wall panels. (15th May 2017) - Fernando, P.L.N.; Jayasinghe, M.T.R.; Jayasinghe, C.
Highlights: A lightweight foam concrete has been made with EPS where 50% of EPS is mechanically recycled type. The EPS based walls can be used as load bearing walls of single storey construction. These walls can also be used as partition walls of multi storey buildings. It also has a flexural strength comparable with other masonry materials. The lightweight foam concrete wall panel can facilitate rapid construction of walls. Abstract: In a global context where the need for quality housing is increasing with improved standard of living and growing population, the over exploitation of natural resources as building materials is becoming a serious problem. In this context, the conversion of non-bio degradable waste materials to quality building products would be extremely useful. In this research, the use of mechanically recycled Expanded Polystyrene as 50% of the total EPS used in a composite foam concrete panel has been assessed experimentally. The results of the experimental program have been interpreted with respect to various useful structural behaviors in compression and flexure. It is shown that the use of this foam concrete along with cement fiber boards produces a lightweight wall panel that can be used very effectively for load-bearing walls of single storey houses and non-loadbearing walls of multi-storey buildings. These lightweight panels can allow rapid construction while reducing the overall weight of the building.